MEMBINA SEKOLAH YANG MENYENANGKAN: TRANSFORMASI PARADIGMA PENDIDIKAN AKAR RUMPUT YANG SELARAS DENGAN TUJUAN PENDIRIAN BANGSA - Andit Triono; Roro Imas Margitamia; Aisyah Ubaidillah; Desinta Setiani (LPPM UIN Sulthan Thaha Saifuddin Jambi, 2022)
One form of realizing the goal of establishing a nation is the existence of schools. Schools are places for the self-development of the nation's children towards a better quality of civilization. But unfortunately, schools are still not able to display the quality that is evenly distributed in the formation of the nation's children who are well-established both mentally and spiritually. Inequality always occurs in the process and outcomes of education in schools. The solution to this is a paradigm shift in education in schools. Therefore, this paper explains conceptually about the fun school movement program that can be applied in schools. This program can be a movement to change the old paradigm in schools into a newer paradigm, and in the future, we can produce better educational outcomes.